Studi Pembuatan Cincau Hitam Instant - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRAK Instant black jelly or cincau were made by boiling dried "`janggelan" plant in water with the addition of "qi" ashes. After filtration, the liquid was then dried. To make cincau gel from it, the powder were mixed with cassava starch and hot water. The gel was form after cooling the mixture. Instant black cincau were made by mixing 2,7 g cassava starch (either modified or non-modified) and different weight of cincau powder i.e. 0.78, 1.0, and 1.5 g. The properties of gels formed were observed. The best gel was produced from 1.0 g cincau powder and 2.7 g non-modified cassava starch mixed in 100 ml water.